Catalytic Activity in the Hydrocarbon Conversion of Systems Containing Platinum, Nickel, Iron, and Zinc Nanoparticles (Communication 2); Petroleum Chemistry; Vol. 48, № 5 - Velichkina L. M.; Pestryakov A. N. Aleksey Nikolaevich; Vosmerikov A. V.; Tuzovskaya I. V.; Bogdanchikova N. E.; Avalos M.; Farias M.; Tiznado H. (2008, 2008)
The catalytic activity of metal-containing zeolites modified by nanosized Pt, Ni, Fe, and Zn powders was studied in the process of upgrading the petroleum straight-run gasoline fractions. It was found that the introduction of metal nanoparticles into the zeolite increases the catalyst activity and allows the desired product to be obtained at a lower processing temperature. An enhancement of the aromatization reactions of the hydrocarbon feedstock was revealed on the catalyst samples deactivated in the first reaction cycle and calcined in air.